2010
DOI: 10.4137/cgm.s2816
|View full text |Cite
|
Sign up to set email alerts
|

Lipases and Related Molecules in Cancer

Abstract: Lipases are enzymes that catalyze the hydrolysis of lipids. Based on protein structures and sequences, lipases can be classified into different protein families. The majority of conventional mammalian lipases are members of the protein super-families of serine esterases and alpha-beta hydrolases. Differential expression of lipases and related alpha-beta hydrolases in tumor cells has been observed. The physiological or patho-physiological functions of these tumor related enzymes are largely unknown. However, li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 86 publications
(112 reference statements)
0
2
0
Order By: Relevance
“…Different tumour types have been shown to express lipase, and there are reported cases of tumor-derived lipase-related lipase elevation ( 11 - 13 ). It has been shown that lipase activities rapidly decrease after treatment ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different tumour types have been shown to express lipase, and there are reported cases of tumor-derived lipase-related lipase elevation ( 11 - 13 ). It has been shown that lipase activities rapidly decrease after treatment ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Different tumour types have been shown to express lipase, and there are reported cases of tumor-derived lipase-related lipase elevation (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%